Optimizing LED spectrum fitting using double Gaussian functions - Liu, Jianxiao; Su, Mingmin; Du, Jingjing; Jiang, Yan; Liu, Xiaolan; Deng, Ruijie; Yao, Ziyue; Shen, Jiaqi; Liu, Xin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
In order to minimize errors during the LED spectrum fitting process and achieve a closer match between the fitted spectrum and the target spectrum, a method employing double Gaussian functions for fitting is proposed. This approach, in comparison to the widely applied modified Gaussian model, avoids issues such as sidelobe uplift when dealing with narrow-band LED spectra. It demonstrates effective fitting for narrow-band LED spectra, exhibiting higher fitting accuracy at the bottom of the spectrum compared to the simple Gaussian model. Moreover, this fitting method introduces no additional fitting variables. The model is constructed by combining two Gaussian functions with weighted summation, and optimizing the weighted coefficients of the two Gaussian functions achieves the best fitting results. Finally, the proposed model is applied to fit various LED spectra, yielding satisfactory results. The outcomes indicate that the overall fitting performance of the double Gaussian model surpasses that of the Gaussian model and the modified Gaussian model.
Optica Applicata, Vol. 54, 2024, nr 3, s. 353-363
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; LED; spectrum fitting; Gaussian functions